2019
DOI: 10.1108/bfj-05-2019-0326
|View full text |Cite
|
Sign up to set email alerts
|

The role of consumer ethnocentrism, country image, and subjective knowledge in predicting intention to purchase imported functional foods

Abstract: Purpose The purpose of this paper is to examine the role of consumer ethnocentrism, country image, functional food image, subjective knowledge and health consciousness in predicting purchase intention of imported functional foods using the theory of planned behavior. Design/methodology/approach A total of 361 Chinese consumers from 20 to 60 year old who have purchased Korean functional foods participated in this study using an online survey. Structural equation modeling was performed to examine the hypothese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
75
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 51 publications
16
75
1
2
Order By: Relevance
“…This result shows that the product country image had a positive and significant impact on brand image. This study confirms the results of previous studies that state that country product image has a positive and significant effect on the brand image (Haque et al, 2015;Xin & Seo, 2019;Hien et al, 2020). Perceptions of the quality of a country's production can positively impact the brand image of a product.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This result shows that the product country image had a positive and significant impact on brand image. This study confirms the results of previous studies that state that country product image has a positive and significant effect on the brand image (Haque et al, 2015;Xin & Seo, 2019;Hien et al, 2020). Perceptions of the quality of a country's production can positively impact the brand image of a product.…”
Section: Discussionsupporting
confidence: 90%
“…Lo et al (2017) stated an influence between product country image on brand image. This proposition is strengthened by the results of empirical research, which showed that there is a significant positive influence between product country image on the brand image (Xin & Seo, 2019;Hien, Phuong, Tran, & Thang, 2020). Thus H4, product country image will have a significant positive effect on brand image.…”
Section: Product Country Image and Brand Imagementioning
confidence: 95%
“…Moreover, technology awareness is emphasized in studies on consumers' intention of purchasing genetically modified food (Zhang et al, 2018). Country of origin (COO) is another frequently discussed factor in studying consumers' intention of purchasing fresh food, foreign food, Halal food, and imported functional food (Holdershaw & Konopka, 2018;Muhamad et al, 2017;Sagheb et al, 2020;Xin & Seo, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For the perceived behavioral control construct, three items were adopted to measure the degree of ability of the individual to perform a behaviour (Dangi et al, 2020;Jin Ma, Littrell & Niehm, 2012;Zhou et al, 2013). For the purchase intention construct, three items were adopted to measure the willingness or readiness of purchasing fraudulent honey (Dangi et al, 2020;Jin Ma et al, 2012;Xin & Seo, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…TPB has been applied widely and successfully in many studies as a theoretical framework from which to examine the purchase intention in halal food consumption (Amalia et al, 2020;Lim at al., 2020;Marmaya at al., 2019), organic food consumption (James et al, 2019;Mohammed, 2020;Teng & Wang, 2015), functional food consumption (Xin & Seo, 2019), genetically modified food consumption (Rabbanee et al, 2020;Zheng et al, 2017;Zhu et al, 2018), green food consumption (Amin & Tarun, 2020), ethnic food consumption (Ahmad et al, 2019) and counterfeit products (Fernandes, 2013). Hence, the TPB model is deemed suitable as the theoretical foundation for this research to understand honey buyers' purchase intention.…”
Section: Theoretical Framework -Theory In Support Of Intention To Purchasementioning
confidence: 99%